2018
DOI: 10.1108/hff-11-2016-0459
|View full text |Cite
|
Sign up to set email alerts
|

Biomass pyrolysis modeling of systems at laboratory scale with experimental validation

Abstract: Purpose Thermochemical conversion processes are one of the possible solutions for the flexible production of electric and thermal power from biomass. The pyrolysis degradation process presents, among the others, the interesting features of biofuels and high energy density bio-oil production potential high conversion rate. In this paper, numerical results of a slow batch and continuous fast pyrolyzers, are presented, aiming at validating both a tridimensional computational fluid dynamics-discrete element method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Zhu et al [596] simulated the fluid flow in a horizontal screw decanter centrifuge as well as the solid concentration distribution. They [597] reported that the 3D unsteady computation with a moving mesh is effective in studying the solid concentration distributions in a fast pyrolysis screw reactor.…”
Section: Fixed Bed Reactorsmentioning
confidence: 99%
“…Zhu et al [596] simulated the fluid flow in a horizontal screw decanter centrifuge as well as the solid concentration distribution. They [597] reported that the 3D unsteady computation with a moving mesh is effective in studying the solid concentration distributions in a fast pyrolysis screw reactor.…”
Section: Fixed Bed Reactorsmentioning
confidence: 99%
“…Hydrogen allows a useful way of storing the surplus power generated by photovoltaics and wind [7]. Moreover, in place of combustion [8,9], the gasification of waste, biomass, and coal [10,11] provides a useful procedure for efficient and clean conversion, whereby the product synthesis gas (syngas) contains rather considerable portions of hydrogen. Furthermore, there is a developing tendency in hydrogen production using nuclear energy [12].…”
Section: Introductionmentioning
confidence: 99%
“…1b, one can see that oxygen penetrates into the fuel jet along the lift-off distance, and, is, then, rapidly consumed by the combustion reactions starting at the flame root, causing a local oxygen depleted zone. Inspecting the data of Wu et al [6] one can deduce that the measured lift-off heights in their dependence to the temperature of the coflow-stream can be represented by the following relationship with a quite good accuracy Table 4, for different coflow temperatures.…”
Section: Isothermal Turbulent Flowmentioning
confidence: 91%
“…Hydrogen offers an attractive alternative for storing excess energy in power generation from photovoltaics and wind energy. Furthermore, instead of combustion [5] the gasification of waste, biomass and coal [6] offers good possibilities for efficient and clean power generation. The so-called synthesis gas (syngas), which results as the product of gasification, contains, in addition to carbon monoxide and small fractions of methane, rather significant amounts of hydrogen.…”
Section: Introductionmentioning
confidence: 99%